Isolation and Identification of Bacteria from the Oral Cavity of Monitor Lizard (Varanus bengalensis) (Advances in Applied Biological Research, 2024)
The current research was carried out in the Kasur district, Punjab, Pakistan with the duration of July 2021 to June 2022. The purpose of study was to isolate and identify the bacterial community in the oral cavity of monitor lizard (Varanus bengalensis). As monitor lizards are ectotherm reptiles so they spent most of their winter season from November to March in hibernation. So, sampling is done before and after the hibernation period. Ten specimens were captured from the study area by the direct encounter and also using hand nets and pitfall traps. The collected samples were transferred to the University of Veterinary Animal Sciences, Ravi Campus, Pattoki at the Postgraduate Lab, Department of Wildlife and Ecology. Specimens were handled with care to aviod injury. The cotton-tipped swab stick was used to collect a saliva sample from the oral cavity by using a sterile mouth gag. At least three cotton swab samples were taken from each specimen.Each swab sample was stored in sterile buffered peptone water in falcon tubes at -4º C. The solution from the tubes was streaked over Nutrient agar (NA), Mannitol Salt (MS) agar, Xylose Lysine Deoxycholate (XLD) agar and Trypticase Soya agar with 5% Sheep Blood agar. All of the plates were cultured at 36±°C in an incubator for 24–48 hours. Gram staining was used to identify descriptive colony morphology. Isolates were identified primarily based on colony morphology on selective media, Gram nature, motility test, and pigment production. For possible identification, the selected colonies were sub-cultured on nutrient agar and Trypticase Soya agar (TSA). After that, isolated biochemical tests were carried out in order to identify them. Three most abundant bacterial species were investigated in present study including Salmonela typhi, Staphylococcus aureus and Pseudomonas aeruginosa their relative abundance would be statisticaly analyzed. Accordingly Salmonela typhi contained 43.33%, Staphylococcus aureus contained 46.67% and Pseudomonas aeruginosa contained 13.33%.
Keywords: Varanus; Pathogens; Zoonotic; Virus; Fungi